The Relationship Between Religious Coping Styles, Perceived Stress and Attitudes Towards Death Among Individuals With Relatives in Intensive Care: A Path Analysis - Bahcecioglu Turan, Gulcan; Karaaslan, Fatma; Ozer, Zulfunaz (Wiley, 2025)
Background Individuals with relatives in intensive care face high psychological distress. Religious coping styles and perceived stress may influence their attitudes towards death, yet the mechanisms of this relationship remain unclear. Aim The study was conducted to examine the relationship between the religious coping styles of individuals with relatives in intensive care, their perceived stress and their attitudes towards death and to investigate the mediating role of perceived stress in the relationship between religious coping styles and attitudes towards death. Study Design This descriptive and cross-sectional study was conducted between March 1, 2023 and March 3, 2025 with individuals who had patients in the intensive care units of a city hospital located in eastern Turkey. Data collection tools included a Personal Information Form, Religious Coping Scale (RCS), Perceived Stress Scale (PSS) and Death Attitudes Profile-Revised (DAP-R).Results Of the 350 individuals invited to participate, 245 completed the study, yielding a response rate of 70.0%. In the study, the mean positive coping score was 18.26 +/- 4.87, and the mean negative coping style score was 20.43 +/- 4.65. The mean PSS score was 32.28 +/- 12.02, the mean Perceived Insufficient Self-Efficacy Perception score was 15.03 +/- 6.61, and the mean Perceived Stress/Distress score was 17.25 +/- 6.85. The mean DAP-R score was 114.31 +/- 22.79, the mean Neutral Acceptance-Approach Acceptance score was 51.32 +/- 11.56, the mean Avoidance Acceptance score was 22.43 +/- 4.71, and the mean Fear of Death and Death Avoidance score was 40.55 +/- 10.34. Perceived stress was found to play a mediating role in the effect of positive coping on attitude towards death (beta = 0.352; (-0.675X -0.522)), and the perceived stress scale was found to strengthen the positive effect on attitude towards death (beta = 0.722). Perceived stress was found to play a mediating role in the effect of negative coping style on attitude towards death (beta = 0.161; (-0.310X -0.522)), and the perceived stress scale was found to strengthen the positive effect on attitude towards death (beta = 0.466). Conclusion It has been observed that participants use negative coping styles more frequently and have moderate levels of perceived stress and attitudes towards death. Positive coping styles increase attitudes towards death, but a significant part of this effect occurs through perceived stress. It can be concluded that individuals develop a healthier awareness of death despite stress or through stress and tend to accept death. Relevance to Clinical Practice Understanding how religious coping and stress affect death attitudes can help healthcare professionals provide more targeted psychological and spiritual support to families of intensive care patients.
Keywords: attitude towards death; intensive care; nursing; religious coping; stress